Long term effects of locomotor training in spinal humans. Issue 1 (1st July 2001) - Wirz, M; Colombo, G; Dietz, V
Abstract : The long term effects of locomotor training in patients with spinal cord injury (SCI) were studied. In patients with complete or incomplete SCI coordinated stepping movements were induced and trained by bodyweight support and standing on a moving treadmill. The leg extensor muscle EMG activity in both groups of patients increased significantly over the training period, associated with improved locomotor ability in those with incomplete SCI. During a period of more than 3 years after training, the level of leg extensor EMG remained about constant in incomplete SCI in those who regularly maintained locomotor activity. By contrast the EMG significantly fell in those with complete SCI. The results suggest a training induced plasticity of neuronal centres in the isolated spinal cord which may be of relevance for future interventional therapies.